2023
DOI: 10.3390/healthcare11050765
|View full text |Cite
|
Sign up to set email alerts
|

Child and Adolescent Mental Health during the COVID-19 Pandemic: Challenges of Psychiatric Outpatient Clinics

Abstract: Background: Worldwide national surveys show a rising mental health burden among children and adolescents (C&A) during COVID-19. The objective of the current study is to verify the expected rise in visits to psychiatric outpatient clinics of C&A, especially of new patients. Methods: a cross-sectional study focusing on visits as recorded in electronic medical records of eight heterogeneous C&A psychiatric outpatient clinics. The assessment was based on visits held from March to December of 2019 (befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The overall number of ADHD patients ≤26 years decreased in 2020 compared to pre-pandemic, with a marked drop among the elementary and adolescent populations. Consistently, studies by other groups demonstrated a significant decrease in psychiatric visits and pharmacotherapy in the child and adolescent populations in 2020 in comparison to 2019 (21). Furthermore, a 70% decrease in referrals for school-based behavioral health services was noted from 2018 to 2020 (22).…”
Section: Discussionsupporting
confidence: 67%
“…The overall number of ADHD patients ≤26 years decreased in 2020 compared to pre-pandemic, with a marked drop among the elementary and adolescent populations. Consistently, studies by other groups demonstrated a significant decrease in psychiatric visits and pharmacotherapy in the child and adolescent populations in 2020 in comparison to 2019 (21). Furthermore, a 70% decrease in referrals for school-based behavioral health services was noted from 2018 to 2020 (22).…”
Section: Discussionsupporting
confidence: 67%
“…One wonders whether intervening in these cases necessarily corresponds to a forced hospitalization in a psychiatric facility or if it is possible to carry out other types of treatment, for example by carrying out a home intervention over a medium-short period (days or a few weeks). Forced hospitalization is a violent tool for those who are subjected to it, and often the patient's rehabilitation measures do not allow them to find a home with their family that can accommodate them once hospitalization is over (49)(50)(51) The hope for the future is to be to be able to nourish and nurture a global model of community mental health intervention (52) by training professional staff in a holistic conception of mental distress and social stigma (53-55), also educating society to request and integrate psychiatric and psychosocial interventions (56) with support from the third sector, ensuring the continuity of care in the family and community after discharge from hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, local scientific literature is still scarce (57)(58)(59), there are no studies or data on mandatory psychiatric treatments in China or that collect experiences of mental health professionals. Another limitation concerns the fact that this exploratory study does not specifically concern mental health in childhood or adolescence (56). Another limitation concerns the generalizability of the data, the A big problem is that our hospital accepts patients from half of Greece as some regional hospitals still do not accept involuntary patients.…”
Section: Limitationmentioning
confidence: 99%
See 1 more Smart Citation